2018
DOI: 10.4067/s0718-95162018005001903
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Boron on pepper plants nutritional status and nutrient efficiency

Abstract: Boron may affect total uptake of various nutrients and their nutrient use efficiency (NUE) which results in high productivity and low fertilizer cost. Therefore, the objective of this study was to investigate the effect of boron concentration in nutrient solution on total uptake of the various nutrients and their utilization efficiency in pepper plants (Capsicum annuum L.). Four cultivars (Osho, Solario, Odysseo and Arlequin) were treated with 0.5-10 mg B L -1 . Each treatment included five replications with 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
(25 reference statements)
0
9
0
1
Order By: Relevance
“…As previously mentioned, Exactyon AG 18:5:13 gave significantly higher nut yields than the control. Previous studies have highlighted the importance of B for chestnut (Portela et al 2011(Portela et al , 2015 and In columns, separated by year, means followed by the same letter are not significantly different by Tukey HSD test (α = 0.05) several other dicot species (Liakopoulos et al 2005;Soyergin 2010;Sarafi et al 2018;Arrobas et al 2019). This result also suggests that part of the increase in nut productivity might be due to the better B nutrition of the trees fertilized with Exactyon AG 18:5:13.…”
Section: Discussionmentioning
confidence: 52%
“…As previously mentioned, Exactyon AG 18:5:13 gave significantly higher nut yields than the control. Previous studies have highlighted the importance of B for chestnut (Portela et al 2011(Portela et al , 2015 and In columns, separated by year, means followed by the same letter are not significantly different by Tukey HSD test (α = 0.05) several other dicot species (Liakopoulos et al 2005;Soyergin 2010;Sarafi et al 2018;Arrobas et al 2019). This result also suggests that part of the increase in nut productivity might be due to the better B nutrition of the trees fertilized with Exactyon AG 18:5:13.…”
Section: Discussionmentioning
confidence: 52%
“…In the literature, information on the relationships between B-related growth conditions and the homeostasis of the other nutrients is lacking (Tariq and Mott, 2007). In fact, conflicting results have been obtained using different crop species and growth techniques, and also analyzing various plant parts at different growth stages (Lombin and Bates, 1982;Singh and Singh, 1984;Carpena and Carpena-Ruiz, 1987;Mozafar, 1989;Agbenin et al, 1990;Zhou et al, 2014;Sarafi et al, 2018). Unfortunately, to our knowledge, nutrient content measurements have never been carried out in grapevines under B deprivation.…”
Section: Effect Of B Deficiency and Gpgv Infection On Nutrient Contentsmentioning
confidence: 99%
“…According to Eggert and von Wirén (2017), nutritional status B causes coordinated changes in plant hormone metabolism as a prerequisite for an adjusted growth response. In this context, it was observed that B influenced the nutritional status and nutritional efficiency in pepper plants, with different responses depending on genotype, B concentration and the nutrient (SARAFI et al, 2018). Thus, B deficiency in K+B-treatment could have promoted the retranslocation in cherry tomato plants as a physiological response, such as observed in radish plants (TARIQ;MOTT, 2006).…”
Section: Resultsmentioning
confidence: 99%